BIOLOGICAL REMOVAL OF Cr (VI) FROM INDUSTRIAL WASTEWATER (AEROBIC & ANAEROBIC CONDITION) - A.R. Mesdaghinia; K. Taghavi (Tehran University of Medical Sciences, 1996)
This Research was conducted in continuous flow bench scale Fixed Activated sludge (FAS) and Anaerobic Filter (AF). The main objective of the research was to study the feasibility and efficiency of the mentioned systems for Cr (VI) removal. In Fas reactor, Cr (VI) was adsorbed from influent to MLSS in the range of 89 to 99 percent and the adsorption followed freundlich isotherm. In AF reactor, Cr (VI) was reduced to Cr(III). The reduction rate in these parts was from 81 to 99 percent.